THE SYSTEM CO2-N2 AT HIGH PRESSURE AND APPLICATIONS TO FLUID INCLUSIONS - Kooi M.E.; Schouten J.A.; van den Kerkhof A.M.; Istrate G.; Althaus E. (My University, 1998)
Postulated fluid-fluid immiscibility of 50-50% CO2-N2 mixtures has been checked by high-pressure experiments (<5 gpa; <400 k) and could be rejected. the implications for interpretation of high-density fluid inclusions (<42 cm3/mole) in eclogite and granulite-facies rocks are discussed: only models based on LG-immiscibility are applicable for molar volume calculations also in the very-high-pressure range. The position of the critical curve for CO2-N2 could be more accurately determined with the help of experimental and fluid inclusion data. The S2-F isopleth and the three-phase (S1S2F) line have been established for 50.6% N2 composition.